Protective aluminide coating by pack cementation for Beta 21-S titanium alloy. (November 2019) - Chaia, N.; Cossu, C.M.F.A.; Ferreira, L.M.; Parrisch, C.J.; Cotton, J.D.; Coelho, G.C.; Nunes, C.A.
Highlights: TiAl3 coating was deposited on titanium alloy Beta-21S by pack cementation with a cement activated by CrCl3 . Thermodynamic analysis was successfully used to predict mechanisms of the coating formation. Elevated oxidation resistance of the coating was demonstrated through isothermal oxidation tests at 750 and 850 °C. Abstract: Pack cementation method was used to form high activity aluminide coating on titanium alloy Beta-21S using a cement activated by CrCl3 at 760 °C for a period of 9 h. Thermodynamic computations showed that growth mechanism of TiAl3 occurs in tree steps involving different chemical reactions. The effectiveness of the TiAl3 coating to protect Beta-21S alloy was demonstrated through oxidation tests performed at 750 and 850 °C during 300 h. The elevated resistance against oxidation of the TiAl3 layer is provided by a protective Al2 O3 scale having low growth kinetics.